„Heterogeniczność przestrzeni miejskiej w Królestwie Polskim i Rzeczypospolitej Obojga Narodów w epoce przedprzemysłowej”, Toruń, 10–11 kwietnia 2014 r. - Czaja, Roman; Noga, Zdzisław (Kwartalnik Historii Kultury Materialnej, 2015)
“THE HETEROGENEITY OF URBAN SPACE IN THE KINGDOM OF POLAND AND THE POLISH-LITHUANIAN COMMONWEALTH IN THE PRE-INDUSTRIAL ERA”, TORUŃ, 10–11 APRIL 2014 The Urban History Team of the Committee of Historical Sciences of the Polish Academy of Sciences has proposed taking a fresh look at the issue of heterogeneity of the communal town in response to new methodological approaches, which interpret space not only as the context ofsocial processes but also as a product of human activities and conceptions. Such an approach leads to enriching the research questionnaire with questions on the shaping of urban space via assigning its particular social and economic functions, via rules and norms, and via symbolic coding and perception. It has long been a standard in exploring the towns of the pre-industrial period to involve representatives of various disciplines. Interdisciplinary research is also a basic requirement in studies inspired by historical anthropology. Therefore, the project that we are presenting here included historians, archeologists, art historians and urban planners. The articles gathered in this volume are based on presentations delivered and discussed by the members of the team and invited speakers during a conference in Toruń held on 11–12 April 2014. The papers include both problem studies, analyzing certain phenomena against a wide comparative background of Central and Eastern Europe, and analytical studies, exemplifying the issue of heterogeneity with cases of towns from Lesser Poland, Silesia, Ruthenia and Royal Prussia.